Development of Interactive Android Application-Based Learning Media to Improve Students' Understanding of Atomic Structure Material in SMA/MA - Ginting, Cintami Ananta; Sagala, Vincencia Friandini; Lubis, Fitriani (CV. Rayyan Dwi Bharata, 2024)
This research uses a descriptive development approach to develop or perfect products in the education sector. The focus is on developing knowledge through the process of creating or improving products, both hardware such as books and learning aids, and software such as computer programs and educational models. The main objective of this development is to develop Kima learning media based on Android applications with the help of Google Site and AppsGeyser. The result of this research is an Android application product for SMA/MA Class , and dissemination. The results of the questionnaire show that the ATOMIC Application was well received by the majority of students, especially in terms of ease of understanding the material and its accessibility. As many as 86.7% of students felt that this application was very helpful in understanding learning, and 80% stated that this application was easy to access and had complete and useful content.